Clinical profile of systemic lupus erythematosus among children less than 12 years - Andy, Senthil Kumar; Kandasamy, Elayaraja (International Journal of Contemporary Pediatrics, 2018)
Background: Systemic lupus erythematosus (SLE) is an episodic multisystem autoimmune disease characterized by widespread inflammation of blood vessels and connective tissues and by the presence of antinuclear antibodies especially antibodies to native double stranded DNA. The aim was to study the clinical profile of SLE among children less than 12 years attending an urban referral hospital, SLEDAI scoring at onset and follow up at 1 year and SLICC/ACR damage index at 1 year. Methods: A descriptive, prospective and observational study was conducted in Medical, Nephrology, Rheumatology OPD wards, in ICH and HC, from November 2007 to August 2009 among all children diagnosed to have SLE. Results: In this study there were 50 cases over the last 2 years. Majority of the children were diagnosed within a year of their initial manifestation. The mean age at the time of onset of symptoms was 7.94 years. Female to male ratio in our study is 2.5:1. Conclusions: Efforts should be directed in diagnosing at earlier stage itself for better outcome. SLEDAI and SLICC/ACR DI can be incorporated in routine follow up to detect mild to moderate and severe flare and extent of organ damage.